Treatment With Calcineurin Inhibitor FK506 Attenuates Noise-Induced Hearing Loss - He, Zu-Hong; Pan, Song; Zheng, Hong-Wei; Fang, Qiao-Jun; Hill, Kayla; Sha, Su-Hua (Frontiers in Cell and Developmental Biology, 2021)
Attenuation of noise-induced hair cell loss and noise-induced hearing loss (NIHL) by treatment with FK506 (tacrolimus), a calcineurin (CaN/PP2B) inhibitor used clinically as an immunosuppressant, has been previously reported, but the downstream mechanisms of FK506-attenuated NIHL remain unknown. Here, we showed that CaN immunolabeling in outer hair cells (OHCs) and nuclear factor of activated T-cells isoform c4 (NFATc4/NFAT3) in OHC nuclei are significantly increased after moderate noise exposure in adult CBA/J mice. Consequently, treatment with FK506 significantly reduces moderate-noise-induced loss of OHCs and NIHL. Furthermore, induction of reactive oxygen species (ROS) by moderate noise was significantly diminished by treatment with FK506. In agreement with our previous finding that autophagy marker microtubule-associated protein light chain 3B (LC3B) does not change in OHCs under conditions of moderate-noise-induced permanent threshold shifts, treatment with FK506 increases LC3B immunolabeling in OHCs after exposure to moderate noise. Additionally, prevention of NIHL by treatment with FK506 was partially abolished by pretreatment with LC3B small interfering RNA. Taken together, these results indicate that attenuation of moderate-noise-induced OHC loss and hearing loss by FK506 treatment occurs not only via inhibition of CaN activity, but also through inhibition of ROS and activation of autophagy.